IMPORTANCE OF ULTRASOUND INVESTIGATION IN THE DIAGNOSIS OF UTERINE APPENDAGE TORSION - Игорь Юрьевич Пеганов; Татьяна Васильевна Третьякова; Светлана Владимировна Шрамко (The Publishing House Medicine and Enlightenment, 2020)
The article presents the results of the analysis of the clinical case of the torsion of the uterine appendages with the erasure of the clinical picture lasting 3 months. Ultrasound diagnostic capabilities in the correctness of accurate diagnosis and choice of adequate treatment are shown. The objective is substantiation of the choice of the tactics for organ-preserving surgical intervention in the torsion of the uterine appendages based on ultrasound investigation. Conclusions. Organ-preserving tactics for surgical treatment of the torsion of uterine appendages is possible when the disease is several months old. The main sign of the ovarian torsion was the presence of spirally twisted vessels inside the vascular pedicle of the ovary, which was detected in the color Doppler mapping mode, which allowed correctly diagnosing this pathological condition.